The Role of Monocyte Distribution Width (MDW) in the Prediction of Death in Adult Patients with Sepsis - Dimitrios Theodoridis; Angeliki Tsifi; Emmanouil Magiorkinis; Xenofon Tsamakidis; Apostolos Voulgaridis; Evgenia Moustaferi; Nikoletta Skrepetou; Sotirios Tsifis; Anastasios Ioannidis; Efstathios Chronopoulos; Stylianos Chatzipanagiotou (Microorganisms)
Sepsis is a life-threatening condition; it is a major cause of hospital mortality worldwide and it constitutes a global health problem. This research investigates the use of MDW as a predictor for septic patients. This was a double-center prospective cohort study of adult septic patients. Septic patients were identified and were categorized into two categories: those who improved and those who died. Blood was drawn from the patients three times, on the first, third, and fifth day of their admission to the hospital. MDW was evaluated as a biomarker to predict patient outcome. In addition, existing inflammatory markers were recorded in all patients. The MDW was able to predict patient’s outcome. The average MDW was found to be significantly higher in patients who died in all records. For example, an MDW value of 28.4 on the first day of admission to the hospital was shown to be the best cut-off value in determining fatal outcomes; receiver operating characteristic (ROC) analysis revealed an area under the curve value of 0.71 (95% Confidence Interval-CI: 0.57–0.84) with a sensitivity of 64.7% and a specificity of 88.2%. In conclusion, MDW, in addition to being a marker that can quickly detect sepsis more effectively than other biomarkers, which is proven by numerous studies, could also be used as an indicator to predict patient outcome. This work is an attempt in that direction.